2017
DOI: 10.3389/fpls.2017.00313
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Allometric Relationships in Leaves of Young Rapeseed (Brassica napus L.) Grown at Different Temperature Treatments

Abstract: Functional–structural plant modeling (FSPM) is a fast and dynamic method to predict plant growth under varying environmental conditions. Temperature is a primary factor affecting the rate of plant development. In the present study, we used three different temperature treatments (10/14°C, 18/22°C, and 26/30°C) to test the effect of temperature on growth and development of rapeseed (Brassica napus L.) seedlings. Plants were sampled at regular intervals (every 3 days) to obtain growth data during the length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
1
3
0
2
Order By: Relevance
“…Samples were collected at 0 (control/CK), 1, and 7 days after the treatment. Our findings were parallel with a recent report (Tian et al, 2017), which found that rapeseed CK plants did not show any significant difference in morphological attributes when harvested under different temperatures and light intensities. Thus, only one CK for the entire analysis was kept.…”
Section: Methodssupporting
confidence: 92%
“…Samples were collected at 0 (control/CK), 1, and 7 days after the treatment. Our findings were parallel with a recent report (Tian et al, 2017), which found that rapeseed CK plants did not show any significant difference in morphological attributes when harvested under different temperatures and light intensities. Thus, only one CK for the entire analysis was kept.…”
Section: Methodssupporting
confidence: 92%
“…All temperature data were also significantly correlated with crisp mouthfeel (r = 0.527; p = <0.0001). Previous research and modelling of rapeseed plants has shown that growth temperature significantly impacts leaf morphology; particularly leaf length and thickness [34]. This may partly explain why rocket leaves are perceived as crispier in summer and autumn months compared with winter ( Supplementary Figure S2).…”
Section: Growing Temperaturementioning
confidence: 93%
“…FSPM, bitki büyüme ve gelişimi için bilgi sağlayan, belirli bir bitki türü için olmayıp C3 fotosentezinin gerçekleştiği bütün bitkilere uygulanabilen bir model yaklaşımdır. Çalışma sonucunda elde edilen 3D yapılar ile organogenetik ve morfogenetik yapı arasındaki ilişkiler açığa çıkarılmıştır [20].…”
Section: Yaprakta Gerçekleştirilen Fenotiplendirme çAlışmalarıunclassified